Mengurai Sosiologi Empiris Berger dan Luckmann sebagai Konstruksi Pengetahuan - Marde Christian Stenly Mawikere; Sudiria Hura (Institut Agama Kristen Negeri Manado, 2022)
This article describes the theory of the sociology of knowledge from Peter Berger and Thomas Luckmann which is reviewed in their best-selling book entitled “The Social Construction of Reality: A Treatise in the Sociology of Knowledge”. The research was conducted by conducting a